Aquaculture Sector Review : Armenia - International Finance Corporation (Washington, DC, 2015)
This aquaculture sector review (with supply chain mapping) has been implemented within the framework of the International Finance Corporation (IFC) Armenia investment climate reform project implemented by the World Bank Group trade and competitiveness global practice, in partnership with Austria’s federal ministry of finance and Hungarian partnership funding and Hungary Export Import (EXIM) Bank. This project aims to contribute to improving the country’s investment climate and thereby to attract investments into selected branches of its economy. This aquaculture supply chain review aims to: (1) identify issues now present in the fish supply (export) chain, specifically pinpointing market imperfections as well as legal and regulatory obstacles; (2) develop recommendations to resolve the problems and challenges so identified, and thus contribute to the improvement of the business and investment environment by reducing costs and increasing productivity; and (3) contribute to enhancing the competitiveness and investment attractiveness of the Armenian fish industry as a whole. This analysis focuses on both policy and market imperfections as well as constraints along the aquaculture supply chain and the impacts these have. The analysis used local and international information sources, official statistical data, and local and international reviews and analytical materials pertaining to aquaculture. The report comprises three sections: an executive summary, a fish export supply chain analysis, and their relevant annexes.